PHYTOCHEMICAL ANALYSIS AND IN VITRO ANTIOXIDANT ASSESSMENT OF CISSAMPELOS PAREIRA LINN. LEAF EXTRACTS - Rani VS; Sruthi S Nair; Supriya R; Rajesh MG; Prita Pillai; K. Jayakumar (Journal of Global Pharma Technology, 2026)
Objective: Cissampelos pareira Linn. is a medicinal plant of the family Menispermaceae. It is commonly known as midwife’s herb and is traditionally used to treat several women’s diseases, including the prevention of miscarriages and uterine haemorrhage. The present study is aimed to evaluate the phytochemical composition and antioxidant potential of leaf extracts of C. pareira. Materials and Methods: Crude extracts were prepared from dried leaf powder using hexane, ethyl acetate, and ethanol as solvents. Qualitative and quantitative phytochemical analyses were carried out using standard procedures. Antioxidant activity was evaluated using the DPPH radical scavenging assay, along with the estimation of total phenol content. Results: Among the crude extracts, the ethanol extract exhibited higher phytochemical content and antioxidant activity compared to the hexane and ethyl acetate extracts. Quantitative analysis revealed that the leaves were particularly rich in flavonoids. The ethanol extract showed the presence of major phytochemicals such as flavonoids and phenolic compounds and demonstrated significant antioxidant activity. Conclusion: The phytochemical characterization and antioxidant evaluation of Cissampelos pareira leaves provide valuable insight into its medicinal potential, supporting its possible application in natural medicine and drug development. Keywords : Cissampelos pareira, antioxidant activity, phytochemical analysis, ethanol extract.